Understanding society through popular music - Kotarba, Joseph A. (New York, NY : Routledge, 2018)
Written for Introductory Sociology and Sociology of Popular Culture courses, this book uses popular music to illustrate fundamental social institutions, theories, sociological concepts, and processes. The authors use music, a social phenomenon of great interest, to draw students in and bring life to their study of social life.
The sociology of popular music / Joseph A. Kotarba -- Social interaction / Joseph A. Kotarba -- The family / Joseph A. Kotarba -- The self, identity, and the life course / Joseph A. Kotarba -- Youth, deviance, and subcultures / Joseph A. Kotarba -- Religion, politics, and popular music / Joseph A. Kotarba -- Class and gender / Joseph A. Kotarba -- Hip-hop culture and social change / Raphael Travis and Scott W. Bowman -- Music and social media / Christopher J. Schneider -- Business in the music community / Rachel Skaggs and Jonathan R. Wynn -- The globalization of popular music: a focus on women in Poland / Katarzyna M. Wyrzykowska.
Includes bibliographical references (pages 211-226) and index.
Keywords: Popular music -- Social aspects